2018
DOI: 10.1136/bcr-2018-224424
|View full text |Cite
|
Sign up to set email alerts
|

Cholestatic jaundice: a unique presentation leading to the diagnosis of HLH with Hodgkin lymphoma, HIV and EBV

Abstract: Haemophagocytic lymphohistiocytosis (HLH) is a syndrome of dysregulated immune activity with macrophage activation that can manifest as pancytopenia, coagulopathy and other laboratory abnormalities, usually progressing to multiorgan failure and death. This report documents the rarely reported association between HLH and Hodgkin's lymphoma (HL) with simultaneous HIV and Epstein-Barr virus (EBV) and complete resolution with chemotherapy. The patient initially presented with cholestatic jaundice. He was then foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Most of the reported cases of HLH associated with HL were treated with standard ABVD chemotherapy. There is one reported case where BV was used with AVD but only for three cycles due to development of neuropathy 12. Our patient was started on A+AVD from the beginning and finished all six cycles of therapy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Most of the reported cases of HLH associated with HL were treated with standard ABVD chemotherapy. There is one reported case where BV was used with AVD but only for three cycles due to development of neuropathy 12. Our patient was started on A+AVD from the beginning and finished all six cycles of therapy.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, HLH is rarely associated with either B cell lymphomas or HL 11. HLH usually co-occurs with Hodgkin’s lymphoma in male patients and predominantly with mixed cellularity and lymphocyte depletion histological types, both of which are strongly associated with EBV 12…”
Section: Discussionmentioning
confidence: 99%
“…Mustafa Ali et al reported a case of HLH in a patient with concurrent Hodgkin's lymphoma, cytomegalovirus, EBV and Candida infection that was successfully treated by treating the cytokine storm first and Hodgkin's lymphoma afterwards [5]. However, cases have been reported where malignancy-associated HLH is treated by treating the underlying malignancy [4,14]. Shaikh et al reported a case of HLH associated with Hodgkin's lymphoma, HIV and EBV that was successfully treated by treating the Hodgkin's lymphoma directly and showed resolution of symptoms within a few days of chemotherapy [4].…”
Section: Discussionmentioning
confidence: 99%
“…The most common inciting factor for secondary HLH in adults is infection followed by malignancy and autoimmune conditions. Many patients with secondary HLH have multiple risk factors [2][3][4][5][6]. It is important to diagnose not only HLH but also the inciting event as the treatment considerations and prognosis greatly depends on the underlying cause [7].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with another medicine; methimazole, PTU has been considered as more effective in a thyrotoxic crisis [3]. Besides the advantages, PTU treatment shows side effects for the patients such as hair loss, swelling, muscle pains, numbness, and headache in addition to major problems with liver and blood cells [4]. Moreover, although PTU is recommended to be used during pregnancy, there could be harmful effects for the baby [5].…”
Section: Introductionmentioning
confidence: 99%